LncRNA ZEB1-AS1 Regulates Colorectal Cancer Cells by MiR-205/YAP1 Axis - Jin, Zhong (Open Med (Wars), 2020)
BACKGROUND: Recent studies demonstrated that long non-coding RNAs (lncRNAs) were involved in many biological processes. Dysregulated lncRNAs are related to many cancers, including colorectal cancer (CRC). However, the molecular mechanism of lncRNA ZEB1-AS1 in CRC is not clear. METHODS: LncRNA ZEB1-AS1, miR-205, and YAP1 expression were measured by quantitative reverse transcriptase PCR (QRT-PCR). YAP1 protein expression was measured by western blotting. Cell viability was measured by MTT assay. Cell apoptosis was detected by flow cytometry. Luciferase reporter assay was used to confirm the relationship between ZEB1-AS1, miR-205, and YAP1. RESULTS: LncRNA ZEB1-AS1 and YAP1 was upregulated in CRC tissues. The expression of YAP1 was positively correlated with ZEB1-AS1. Knockdown of ZEB1-AS1 inhibited cell viability and induced apoptosis in CRC cell line SW480 and HCT116 which could be reversed by overexpression of YAP1. ZEB1-AS1 targeted and regulated miR-205 which could directly bind to YAP1. Meanwhile, ZEB1-AS1 regulated the expression of YAP1 via modulating miR-205. CONCLUSION: Long non-coding RNA ZEB1-AS1 silencing could inhibit cell proliferation and induce apoptosis of colorectal cancer via regulating miR-205 and YAP1.